Analysis of the DPR'S Policy in Rejecting BPJS Health's Inclusion in the Health Law - Yasin, Hamid Noor; Saptomo, Ade (Devotion : Journal of Research and Community Service, 2024)
The House of Representatives (DPR) as a legislative institution in Indonesia has a very important role in drafting and formulating laws, including approval of laws. In this article, an in-depth analysis will be carried out regarding the DPR's policy in rejecting the inclusion of BPJS Health in the Health Law in Indonesia. The DPR can consider alternative policies or improvements to the health insurance system to make it more effective and sustainable in providing health services to the community. The research aims to provide an insight into the legislative process, policy-making dynamics, and the potential consequences for public health administration and policy. The study will be conducted by combining primary, secondary, and tertiary legal materials (which are secondary data) with primary data obtained in the field, namely DPR Policy Analysis.